Aerial Remote Sensing and Urban Planning Study of Ancient Hippodamian System - Dimitris Kaimaris; Despina Kalyva (Urban Science)
In ancient Olynthus (Greece), an Unmanned Aircraft System (UAS) was utilized to collect both RGB and multispectral (MS) images of the archaeological site. Ground Control Points (GCPs) were used to solve the blocks of images and the production of Digital Surface Models (DSMs) and orthophotomosaics. Check Points (CPs) were employed to verify the spatial accuracy of the products. The innovative image fusion process carried out in this paper, which combined the RGB and MS orthophotomosaics from UAS sensors, led to the creation of a fused image with the best possible spatial resolution (five times better than that of the MS orthophotomosaic). This improvement facilitates the optimal visual and digital (e.g., classification) analysis of the archaeological site. Utilizing the fused image and reviewing the literature, the paper compiles and briefly presents information on the Hippodamian system of the excavated part of the ancient city of Olynthus (regularity, main and secondary streets, organization of building blocks, public and private buildings, types and sizes of dwellings, and internal organization of buildings) as well as information on its socio-economic organization (different social groups based on the characteristics of the buildings, commercial markets, etc.).